2007
DOI: 10.1164/rccm.200608-1125oc
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled Corticosteroids and Risk of Lung Cancer among Patients with Chronic Obstructive Pulmonary Disease

Abstract: Rationale and Objectives: Lung cancer is a frequent cause of death among patients with chronic obstructive pulmonary disease (COPD). We examined whether the use of inhaled corticosteroids among patients with COPD was associated with a decreased risk of lung cancer. Keywords: chronic obstructive pulmonary disease; pharmacoepidemiology; lung cancer; adherence Lung cancer is the most common cause of cancer related death in the United States, and accounts for more deaths each year than breast, prostate, and colore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
151
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(160 citation statements)
references
References 83 publications
8
151
0
1
Order By: Relevance
“…Two retrospective cohort studies suggest that inhaled corticosteroids may be protective against lung cancer [59,60]. A dose-response relationship has been observed between exposure to inhaled corticosteroids and the reduction in the risk of lung cancer.…”
Section: Preventing Lung Cancer In Copdmentioning
confidence: 99%
“…Two retrospective cohort studies suggest that inhaled corticosteroids may be protective against lung cancer [59,60]. A dose-response relationship has been observed between exposure to inhaled corticosteroids and the reduction in the risk of lung cancer.…”
Section: Preventing Lung Cancer In Copdmentioning
confidence: 99%
“…An observational epidemiological study performed on data from patients diagnosed with chronic obstructive pulmonary disease (COPD) found that inhaled corticosteroid use resulted in a lower incidence of lung cancer (Parimon et al 2007). COPD is a risk factor for lung cancer because of its association with smoking and inflammation.…”
Section: The Effects Of Gc Monotherapy On Nsclcmentioning
confidence: 99%
“…Regular use of an inhaled glucocorticoid may reduce the risk of lung cancer among former smokers with COPD [81,82]. However, long-term inhalation of high-dose glucocorticoids did not induce any regression of bronchial dysplasia or secondary markers of carcinogenesis in smokers [83] and did not decrease the risk of lung cancer [84].…”
Section: Lung Cancer Prevention In Copd Patientsmentioning
confidence: 99%